Outcome of patients with negative CT angiography results for arterial occlusion treated with intravenous thrombolysis - Mikulik, Robert; Goldemund, David; Reif, Michal; Aulicky, Petr; Krupa, Petr (Stroke, 2009)
BACKGROUND AND PURPOSE: Stroke patients without evidence of arterial occlusion may not be suitable candidates for thrombolytic therapy. In our study, we investigated the outcomes of patients with negative CT angiography results for arterial occlusion. METHODS: The study included patients treated within 3 hours after symptom onset with intravenous thrombolysis for significant neurological deficit between August 2003 and June 2007. All of the patients were documented with negative CT angiography results for arterial occlusion by independent reviews. Outcome measurements included modified Rankin score at 3 months, incidence of intracranial hemorrhage, and infarction volume on control CT. The predictors of unfavorable outcome (modified Rankin score, 2-6) were identified by multivariate logistic regression. RESULTS: Altogether, 173 patients received intravenous thrombolysis; of those, 138 underwent CT angiography. The CT angiography results were negative for arterial occlusion in 39 (28%) of the patients: mean age, 71+/-10 years; 16 (41%) female; median baseline NIHSS, 11. At 3 months, modified Rankin score of 0 to 1 was achieved in 18 (46%) of the patients; 6 (15%) died; and 3 (8%) had symptomatic parenchymal hemorrhage. The median infarct volume was 1.5 cm(3). The independent predictors of unfavorable clinical outcome were higher age (OR, 1.1; 95% CI, 1.01-1.27), and baseline NIHSS >12 (OR, 18.8; 95% CI, 1.4 to 261). One patient had encephalitis diagnosed. CONCLUSIONS: Negative baseline CT angiography is not uncommon. The risk of intracerebral hemorrhage after thrombolytic therapy for patients without evidence of arterial occlusion is similar to the risk carried in an unselected patient population. Given the prognosis, thrombolytic therapy seems justified; however, etiology other than stroke should be considered.
Keywords: Cerebrovascular Disorders; logistické modely; Female; Tissue Plasminogen Activator; aktivátory plazminogenu; Thrombolytic Therapy; výsledek terapie; ženské pohlaví; Logistic Models; Tomography, X-Ray Computed; cévní mozková příhoda; trombolytická terapie; lidé; Stroke; databáze faktografické; injekce intravenózní; Treatment Outcome; Cerebral Hemorrhage; Humans; cerebrální krvácení; prospektivní studie; Male; fibrinolytika; Aged; Prospective Studies; Arterial Occlusive Diseases; cerebrovaskulární poruchy; Databases, Factual; lidé středního věku; Cerebral Angiography; tkáňový aktivátor plazminogenu; senioři; mužské pohlaví; Plasminogen Activators; arteriální okluzní nemoci; Fibrinolytic Agents; Middle Aged; Injections, Intravenous; mozková angiografie; počítačová rentgenová tomografie